Estudio de caso a un usuario con diagnóstico de cetoacidosis diabética - Encinas-Bojorquez, Jacqueline Alejandra (Universidad de Sonora, 2019)
This case study focuses on a patient in critical condition with medical diagnosis of diabetics ketoacidosis, has been done under the typology for valuation of functional health patterns of Marjo¬ry Gordon and developed under the methodology of the nursing process (PE).  Have been detected the principal human responses from the patient, in order to establish the most appropriate nursing diagnoses in this case, same that are sustained in the taxonomy II of NANDA-I, suitable as individual manifestations of the patient. This analysis require critical thinking that allows us to establish clinical judgments in a successful manner. From this a nursing care plan is developed through the NOC-NIC taxonomies, where expected results in the patient and interventions were established.